The Day-Of-The-Week Effects as Observed at the Kuala Lumpur Stock Exchange and Their Implications on the Efficient Market Hypothesis - Khairon, Rosli (1999)
The Capital Asset Pricing Model relies on the mathematical notion of expected rates of return . It is thus important to determine just how well stock prices mirror the fundamental value of firms. Previous studies on stock returns have revealed certain empirical anomalies and irregularities. Past studies conducted primarily in the US indicated the existence of "day-of-the-week" seasonal anomaly where daily returns for certain days of the week are consistently above or below the average. This paper attempts to observe this phenomenon in the Malaysian stock market by using data of daily index returns. It was found that DOTW effects observed at the KLSE were only statistically significant during periods of economic expansion. A new finding revealed by this study was that Wednesday exhibited the highest mean daily returns at the KLSE as opposed to the finding of Friday having this distinction in earlier studies. However,in agreement with earlier studies; this study discovered that Monday has the lowest mean daily return among the days of the week.Furthermore, it was discovered that Monday persistently recorded negative daily returns. A formal model attempting to explain the anomaly is presented. The implications of the observed anomaly to the Efficient Market Hypothesis is then discussed.